If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 55 = -4r + -9 Reorder the terms: 55 = -9 + -4r Solving 55 = -9 + -4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '4r' to each side of the equation. 55 + 4r = -9 + -4r + 4r Combine like terms: -4r + 4r = 0 55 + 4r = -9 + 0 55 + 4r = -9 Add '-55' to each side of the equation. 55 + -55 + 4r = -9 + -55 Combine like terms: 55 + -55 = 0 0 + 4r = -9 + -55 4r = -9 + -55 Combine like terms: -9 + -55 = -64 4r = -64 Divide each side by '4'. r = -16 Simplifying r = -16
| -2(x+10)=3(2x-4) | | 15y-12(-26.75+1.25y)=321 | | 2(x+7)=x+5 | | 48u^2-70u+25=0 | | (6x+7)(2x-1)= | | 8(11-x)=15 | | 5x+3=-5+2x+20 | | 8u^2+43u-30=0 | | t(t+3)=70 | | 3(8x-2x)+21-x=7x | | 6(1-3m)+4=-6-2(-4+5m) | | 6(x-2.5)/=8-6(3.5+x) | | (6x+7)(1+-2x)= | | 6u^2+31u-30=0 | | 0=2x^2-9x+4 | | -14=c | | 4rcos+rsen=8 | | 8+a=13 | | 4x^2+2x-110=0 | | 9x-3=6x | | 9+8(x+2)= | | 6u^2-53u+40=0 | | (6x+7)(1+2x)= | | X^2-16X+64=y | | 2+(2-6)-2=10 | | -(2.1c-4d)= | | 9x=7y+23 | | 3(9y)= | | 30(2x-1)=6(x+4)+3 | | 7x=x+8x+3 | | 32x+11(5-12x)=21 | | 99=8+7x |